Analisis Faktor yang Berhubungan dengan Kepatuhan Pasien di Kabupaten Banjar - Mustaqimah Mustaqimah; Rina Saputri; Ali Rakhman Hakim; Reny Indriyani (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
Hypertension is still the most common disease in the world. South Kalimantan Province in 2018 became the province with the highest number of hypertension sufferers in Indonesia. Hypertensive patients will undergo hypertension therapy for the rest of their lives so that blood pressure can still be well controlled. Lifelong therapy can reduce patient compliance in taking hypertension drugs; this can result in failed therapeutic goals and lead to the emergence of other diseases such as myocardial infarction and others. The purpose of this study was to analyze sociodemographic factors and clinical factors that may be related to patient compliance in taking hypertension drugs in Banjar Regency. The results showed that the majority of respondents had low compliance in consuming hypertension drugs. The analysis showed that sociodemographic factors such as gender, age, occupation, and place of getting the drug and clinical factors in the form of drugs used and blood pressure control did not show a significant relationship. The education factor shows a p-value < 0.05, which indicates the education factor has a significant relationship.